The Offense Between Negligence of the State Civil Apparatus and the Criminal Act Of Forgery Of Letters In Making Certificates Of Ownership Rights - Budianto, Agus; Nugraha, Dwi Putra; Minerva, Maria; Maukar, Michelle Regine; Laure, Callista; Vandini, Tia (UNIVERSITAS PAKUAN, 2025)
Abstract The State Civil Apparatus (ASN) is a profession in government agencies responsible for providing public services based on good governance principles. However, the actual delivery of these services may not always meet public expectations. Maladministration, including negligence, abuse of authority, and neglect of legal obligations, can create opportunities for criminal acts, such as forgery of letters. This research focuses on the correlation between ASN negligence and the crime of letter forgery in the issuance of certificates of ownership. Through a qualitative approach and case study, the study reveals that deviations from the principles of good governance by ASN could be contributing factors to document forgery. Document forgery reflects the elements of an unlawful act and malicious intent. Despite the availability of legal measures in Indonesia, weak supervision and integrity of human resources hinder prevention and prosecution. The study also examines criminal law in India and the Netherlands to assess the Indonesian legal system. Keywords: Maladministration, Forgery, Comparative Criminal Law